Variant drainage of frontal sinus - Sharma, Anshu; K. V., Amrutha; Abraham, Joseph (International Journal of Research in Medical Sciences, 2017)
Frontal sinuses are drained by front nasal duct. The opening of the front nasal duct is found on the anteromedial aspect of the floor of the sinus. The duct then continues through the ethmoidal labyrinth and enters the ethmoidal groove at the anterior end of the middle meatus. Here we noticed that frontal sinus was draining into the bulla ethmoidalis on both the sides. These anatomical variations affect the drainage and ventilation of Para nasal sinus due to infection lead to stasis of secretion cause recurrent and chronic sinusitis.